Analysis of freight corridors using GPS data on trucks - Flaskou, Mania; Dulebenets, Maxim A.; Golias, Mihalis; Mishra, Sabyasachee; Rock, Robert M. (My University, 2015)
Trucks remain an important link for today's supply chains because the majority of goods in the United States and around the world are delivered to their final destination by trucks. With increasing roadway network congestion, obtaining detailed truck trip data to assist with freight transportation planning and operations is crucial. Recent advances in GPS devices enable various public and private transportation agencies to obtain more precise information about truck travel patterns. The main objective of this study was to develop a methodology for processing raw GPS data and to develop freight performance measures. Two algorithms were proposed to estimate bidirectional link speeds and to analyze truck trips. A case study for the state of Tennessee is presented to evaluate the proposed methodology.
Keywords: Freight Corridors; GPS